Impactos do registro da despesa e receita de IRPJ e CSLL, com base no lucro real, no resultado do período, no setor de serviços médicos: hospitalares, análises e diagnósticos - Vitalli, Hugo do Carmo Misse (2022)
Companies that calculate IRPJ and CSLL based on Actual Profit need to understand the importance that such a calculation method requires specific knowledge, given the complexity involved and due to the numerous tax and accounting laws applicable to the subject. There is a need to understand whether or not the company's accounting operations can affect such calculation, and thus, judge whether they would be subject to adjustments to accounting income to arrive at Taxable Income through the so-called "additions, exclusions and tax offsets". Can IRPJ and CSLL expenses and income in the period result of legal entities that opt for Actual Income can positively or negatively influence the accounting result for the period, and consequently can also influence the composition of the balance of the Retained Earnings or Losses account? The work proposes to answer this question by analyzing the impacts of recording IRPJ and CSLL expenses and income, based on the Actual Profit, on the result for the period, and the consequent impact on the composition of the accumulated Profit/Loss balance of the shareholders' equity of companies under analysis. Chapter 1 brings a brief historical passage, commenting on the origin of taxes, and elucidates the concept of taxes in Brazil today. Chapter 2 discusses corporate income tax and social contribution on net income and brings brief concepts about: tax immunity; IRPJ exemption; calculation basis; calculation period; IRPJ and surcharge rate; and monthly income tax deductions. Chapter 3, in turn, conceptualizes and provides information about the currently existing methods for calculating the IRPJ and CSLL, such as the Real Income systems; Presumed profit; and Arbitrated Profit. Finally, through the information related to the IRPJ and CSLL of the companies object of analysis, it was found that the adjustments of additions and exclusions to the accounting result, to arrive at the Real Profit, had a fundamental role in the value of expense / income of IRPJ and CSLL in the accounting result, and reflected in different scenarios of composition of the retained earnings or losses account of Shareholders' Equity in the period ended in Sep/2021, as can be seen in Chapter 4